Rational Design of Metal-Organic Frameworks for Pancreatic Cancer Therapy from Machine Learning Screening to In Vivo Efficacy - Melle, Francesca (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.